Pengaruh Diskon Dan Ulasan Produk Terhadap Keputusan Pembelian Di Aplikasi Shopee (Studi Kasus Mahasiswa S1 Manajemen Unidha) - Prabu Ramadhan; Tiara Turay (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the effect of discounts and product reviews on purchasing decisions in the Shopee app (a case study of undergraduate management students at Unidha). The population in this study was 414 undergraduate management students at Dharma Andalas University, Padang. The sample size was calculated using the Raosoft sample size calculator, resulting in a sample size of 104 respondents. Data were obtained by distributing questionnaires, then processed and tested using IBM SPSS Statistics 22. The results of the hypothesis testing indicate that 1) Discounts have a positive and significant effect on purchasing decisions, 2) Product reviews have a positive and significant effect on purchasing decisions, and 3) Discounts and product reviews have a positive and significant effect on purchasing decisions. Furthermore, discounts and product reviews are 67.6% influenced by purchase decisions, while the remaining 32.4% is influenced by other variables not included in this study.